Antibiotics: a risk factor for irritable bowel syndrome in a population-based cohort. (2nd September 2018) - Krogsgaard, Laura Rindom; Engsbro, Anne Line; Bytzer, Peter
Abstract: Objectives: Use of antibiotics affects the composition of the gut microbiome. The microbiome is thought to play a role in development of irritable bowel syndrome (IBS), but antibiotics as a possible risk factor for IBS has not been clarified. We aimed to explore if antibiotics is a risk factor for IBS by investigating use of antibiotics and development of IBS in a cohort from the Danish background population. Materials and Methods: An internet-based web panel representative of the Danish background population was invited to participate in a survey regarding the epidemiology of IBS in 2010, 2011 and 2013. A questionnaire based on the Rome III criteria for IBS were answered at all three occasions. In 2013, a question regarding use of antibiotics in the past year was included. Results: In 2013, use of antibiotics was reported by 22.4% (624/2781) of the population. A higher proportion of individuals with IBS reported use of antibiotics compared with asymptomatic controls [29.0% (155/534) vs. 17.9% (212/1, 184), p  < .01]. For asymptomatic respondents in 2010 and 2011 (n = 1004), the relative risk of IBS in 2013 related with use of antibiotics was 1.9 [95% confidence interval (CI): 1.1–3.1]. Adjusting for sex by logistic regression, development of IBS was predicted by use of antibiotics with an odds ratio of 1.8 (95% CI: 1.0–3.2). Conclusions: Antibiotics is a risk factor for IBS in asymptomatic individuals. Possible mechanisms should be investigated in future studies.